2018
DOI: 10.1159/000492079
|View full text |Cite
|
Sign up to set email alerts
|

Once-a-Day Trazodone in the Treatment of Depression in Routine Clinical Practice

Abstract: Objective: The aim of the study was to evaluate the efficacy, tolerability, and safety of once-a day trazodone tablets (Trittico Prolong® 300 mg) in patients with moderate to severe depression in routine clinical practice. Methods: Men and women ≥18 years old with Montgomery-Åsberg Depression Rating Scale (MADRS) scores > 21 and Clinical Global Impression – Severity (CGI/S) ≥4 were included in this post-authorization, non-interventional, observational prospective safety study, conducted in 8 psychiatric center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…A recent HDRS17 factor reanalysis of the two studies found that the faster antidepressant effects of trazodone were not only exerted, as expected, on the sleep component of depressive symptoms, but also on the cognitive aspects of depression [33]. These results seemed to be in line with a previous report of the rapid antidepressant efficacy of trazodone OAD (1 week) in a clinical practice setting, as measured using the Montgomery-Asberg Depression Rating Scale (MADRS) [37]. Moreover, early studies had already found that trazodone IR resulted in a greater reduction in 1 week treatment at the HDRS as compared to bupropion and fluoxetine [38,39] as well as to trazodone PR vs. a placebo [40].…”
Section: When Antidepressants Take Too Long: the Unmet Needs In The P...supporting
confidence: 84%
“…A recent HDRS17 factor reanalysis of the two studies found that the faster antidepressant effects of trazodone were not only exerted, as expected, on the sleep component of depressive symptoms, but also on the cognitive aspects of depression [33]. These results seemed to be in line with a previous report of the rapid antidepressant efficacy of trazodone OAD (1 week) in a clinical practice setting, as measured using the Montgomery-Asberg Depression Rating Scale (MADRS) [37]. Moreover, early studies had already found that trazodone IR resulted in a greater reduction in 1 week treatment at the HDRS as compared to bupropion and fluoxetine [38,39] as well as to trazodone PR vs. a placebo [40].…”
Section: When Antidepressants Take Too Long: the Unmet Needs In The P...supporting
confidence: 84%
“…23,24 The antidepressant efficacy, combined with improved tolerability and improvements in sleep disturbance observed with trazodone OAD, may have important clinical implications, like enhanced compliance and decreased use of concomitant medications. In fact, the observational study conducted by Češková et al 41 showed that adherence with trazodone OAD formulation was high (>70%) after 21 weeks of treatment. The study also reported a significant reduction in the need for concomitant medications, such as anxiolytics, hypnotics, and other psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients reported improvement in the overall severity of their illness as assessed by the Clinical Global Impression-Severity scale after 6 days of treatment, thus demonstrating that the early improvement observed with trazodone was clinically meaningful. 41,50 This suggests that early onset of antidepressant action is a specific characteristic of trazodone. Early improvement with antidepressants has important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its approval, the antidepressant efficacy and the favorable tolerability profile of trazodone have been confirmed in several pharmacological and clinical studies (27,28). Results have demonstrated that trazodone was as effective as other antidepressant classes in the management of depressive disorders (26, [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%